Methodology of Developing the Strength of Female Wrestlers (Texas Journal of Multidisciplinary Studies, 2023)
This article delves into the methodology of developing the strength of female wrestlers, a crucial aspect of their athletic performance and success in the sport. Drawing upon the latest research and insights from the field of sports science, the study explores training regimens, nutrition strategies, and psychological factors that contribute to enhancing the strength of female wrestlers. By examining the unique physiological considerations and gender-specific training approaches, this article provides a comprehensive guide for coaches, athletes, and sports enthusiasts interested in optimizing the strength development of female wrestlers.